Human Albumin Fragments Nanoparticles as PTX Carrier for Improved Anti-cancer Efficacy - Liang Ge; Liang Ge; Xinru You; Jun Huang; Yuejian Chen; Li Chen; Ying Zhu; Yuan Zhang; Xiqiang Liu; Jun Wu; Qian Hai (Frontiers Media S.A., 2018)
For enhanced anti-cancer performance, human serum albumin fragments (HSAFs) nanoparticles (NPs) were developed as paclitaxel (PTX) carrier in this paper. Human albumins were broken into fragments via degradation and crosslinked by genipin to form HSAF NPs for better biocompatibility, improved PTX drug loading and sustained drug release. Compared with crosslinked human serum albumin NPs, the HSAF-NPs showed relative smaller particle size, higher drug loading, and improved sustained release. Cellular and animal results both indicated that the PTX encapsulated HSAF-NPs have shown good anti-cancer performance. And the anticancer results confirmed that NPs with fast cellular internalization showed better tumor inhibition. These findings will not only provide a safe and robust drug delivery NP platform for cancer therapy, but also offer fundamental information for the optimal design of albumin based NPs.